Pendampingan Penyusunan Paket Wisata Tematik Di Desa Wisata Banaran, Kulonprogo, Daerah Istimewa Yogyakarta - Wijayanti, Ani; Devi Hari Putri, Emmita; Ulumuddin Ahmad Asshofi, Izza; Rahayu, Emik; Yulianto, Atun; Yulianto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Assistance in the preparation of thematic tour packages in Desa Wisata Banaran, Kulonprogo, Daerah Istimewa Yogyakarta Banaran Tourism Village is a newly established tourism village in 2023. The management of Banaran tourism village still has many constraints, especially in the preparation of tourism village packages as the main product of tourism villages. The tourism village preparation assistance program aims to increase the capacity of tourism village managers to develop thematic tour packages that can attract tourists. The assistance is carried out through five stages, namely lectures, simulations, practices, trials, and monitoring and evaluation. The assistance in preparing tour packages resulted in the identification and mapping of tourism potential in the form of tourist objects and homestays. The identification data became a reference in developing thematic tour packages with profitable prices. The tour package preparation assistance program produced six thematic tour packages, namely nature, culture, culinary, history, education, and artificial.